Nano-Heteroepitaxy: An Investigation of SiGe Pillars Coalescence. (1st January 2019) - Mastari, M.; Charles, M.; Bogumilowicz, Y.; Pimenta-Barros, P.; Argoud, M.; Tiron, R.; Papon, A. M.; Muyard, D.; Chevalier, N.; Landru, D.; Kim, Y.; Hartmann, J. M.
Abstract : In this paper, SiGe nano-pillars coalescence was investigated using a 300 mm industrial Reduced Pressure-Chemical Vapor Deposition tool. An integration scheme based on diblock copolymer patterning provided nanometer size templates for the selective epitaxy of SiGe 25% nano-pillars. In order to study coalescence, thicknesses ranging from 20 to 35 nm were grown and samples characterized by Atomic Force Microscopy, X-Ray Diffraction, Scanning Spreading Resistance Microscopy and Transmission Electron Microscopy. The evolution in terms of grain shape, size and number was examined, with individual pillars merging into larger grains above 30 nm thickness. High degrees of macroscopic strain relaxation were obtained at the different stages of nano-pillars merging. Defects such as stacking faults and twins were identified as occurring at the early stages of nano-pillar coalescence.